Rating the United Kingdom: the British government’s sovereign credit ratings, 1976-1978 - Gill, David James (Wiley, 2015)
The UK received its first sovereign credit ratings in 1978. Despite having required financial assistance from the International Monetary Fund only 18 months earlier, the British government managed to secure ‘triple-A’ ratings from both Standard and Poor's and Moody's. Both assessments of creditworthiness reflected improving economic conditions but also British efforts to influence the sovereign ratings process. The Bank of England and the Treasury sought guidance from American investment banks to prepare for the ratings process and then controlled the flow of information available to the rating agencies accordingly, stressing the strengths of the national economy and downplaying the weaknesses. The British government subsequently launched its first bond issue in the New York market to high levels of investor demand. Consideration of these achievements complements the historiography concerning Britain's economic fortunes in the late 1970s. Scrutiny of events also offers a rare glimpse into the confidential sovereign ratings process. Both agencies relied on a combination of quantitative and qualitative evaluations of the UK. In addition, this article highlights the existence of a unique period in the history of sovereign credit ratings. From 1974 to 1985, the ratings industry enjoyed a cautious revival focused principally on ‘triple-A’ borrowers.